Social cognitive theory and viable system model for diagnosing publication productivity - Dhillon, Sharanjit Kaur (2015)
The phrase "publish or perish" is continually in the minds of academic staffs, therefore it is essential for them to keep track of their publication records. Publication is seen to be the main source of evaluation in the academic world. Further, publication criteria are mainly evaluated for purposes of promotion and to access research grants from the institution or government entities. This study analyzes publication performance using academic profiles available in the universities' repository process namely SCIVAL-UTM. With over 1700 profiles, the author was able to identify the publication productivity among the academic staffs of the organization. The basis of this research is to unveil personal, behavioral and environmental factors using social cognitive theory (SCT). It also aims to implement a Viable System Model (VSM) as the diagnostic tool relating to key performance indicators (KPI) delivery on scholarly publications. Through the analysis using VSM, we found a range of aspects including among others, diverse sources and stakeholders which are higher in contrast to the stakeholder's capability to practice these aspects in the KPI delivery. The main criteria in the academic profile being analyzed involved examining the respective positions, in addition to the number of publications produced among the academic staffs.